Rescoring of Patients with Gestational Trophoblastic Neoplasia Using Modified Scoring System By Figo - Taner Turan; Serap Bozok; Nurettin Boran; Nejat Özgül; Sevgi Koç; Gökhan Tulunay; Özlem Kerimoğlu; Faruk Köse (Medical Network, 2006)
OBJECTIVE: The scoring system of GTN determines the treatment modalities. Scoring system was first improved by Bagshawe et al. in 1976. World Health Organisation (WHO) had modified this scoring system in 1983. FIGO reviewed and rev ised the WHO scoring system in 2000. In this study, the change in scores and risk groups of patients scored according to WHO, were analy zed when the patients were re-evaluated according to FIGO STUDY DESIGN: The records of 71 patients with GTN were reviewed between 1994 and 2002. The f irst scoring system that determines the treatment modality was WHO scoring system in all patients. All patients were rescored by the FIGO's modif ied scoring system retrospectively. RESULTS: In this study, 35.2% of 71 patients' score wasn't changed, while increased in 14.1% and decreased in 50.7%. In high-risk group (n=29) by the WHO scoring system the risk score was same in 31% of patients, increased in 27.6% and decreased in 41.4%. In the intermediate-risk group (n=15) risk score was same in 33.3% and decreased in 66.7%. In the low-risk group (n=27) the risk score was same in 40.7%, increased in 7.4% and decreased in 51.9% of patients. CONCLUSION: Today the uncertainty of the scoring systems still remains. The univariant and the multivariant analyses of the studies about the effect of prognostic factors that are used in scoring systems on the treatment success declare different results. The new studies will show the validity of the last scoring system.